Clinical heterogeneity in hereditary haemorrhagic telangiectasia: are pulmonary arteriovenous malformations more common in families linked to endoglin?. Issue 3 (March 1996) - Berg, J N; Guttmacher, A E; Marchuk, D A; Porteous, M E
Abstract : Pulmonary arteriovenous malformations (PAVMs) occur in up to 27% of patients with hereditary haemorrhagic telangiectasia (HHT) and are associated with a rate of paradoxical cerebral embolism at presentation of up to 36%. At least two different loci have been shown for HHT. Mutations in endoglin have been found in some families and the locus designated ORW1. In other families this locus has been excluded. In this paper we confirm that in families linked to ORW1 there is a prevalence of PAVMs among affected members of 29.2%, compared to a prevalence of 2.9% in families in which this locus has been excluded (chi 2 = 19.2, p < 0.001). This information can be used to decide how to screen HHT patients for PAVMs.